Respuesta :

The equation that matches the table is [tex]f(x)=(\frac{2}{3} )^{x}[/tex]

Explanation:

From the table, we can see that this is a geometric progression because the common difference in the y-term is [tex]\frac{2}{3}[/tex]

Thus, [tex]r=\frac{2}{3}[/tex] and [tex]a=\frac{2}{3}[/tex]

To determine the equation, let us substitute the values of r and a in the general form of geometric progression.

The general form of geometric progression is given by

[tex]a_{n}=a r^{n-1}[/tex]

Now, substituting we have,

[tex]a_{n}=\frac{2}{3}\left(\frac{2}{3}\right)^{n-1}[/tex]

Simplifying by adding the powers of similar terms, we get,

[tex]a_{n}=(\frac{2}{3})^{n}[/tex]

Writing it in terms of x, we get,

[tex]f(x)=(\frac{2}{3} )^{x}[/tex]

Thus, the equation that matches the given table is [tex]f(x)=(\frac{2}{3} )^{x}[/tex]